(untitled) (Scientific journal of the Fergana State University, 2023)
An analogue of the Cauchy problem for an iterated multidimensional Klein-Gordon-Fock equation with a time- dependent Bessel operator has been investigated. Applying the generalized Erdélyi-Kober operator the formulated problem has been reduced to the Cauchy problem for the polywave equation. Applying a spherical mean method, an explicit formula for solving this problem for the polywave equation is constructed and based on this solution, an integral representation of the solution of the formulated problem is found.